Analisis Standar Proses Sebagai Upaya Peningkatan Mutu Pendidikan Nasional - Yusup, Bahtian (Universitas Hamzanwadi, 2019)
This study aims to analyze the achievement of Process Standards at SMK Negeri 1 Panjalu, CIamis West Java, this matter is important to be discussed because it is to ensure the achievement of an institution in achieving the intervals of national education standards. This research method uses participatory descriptive research, Partisifan of this study is Wakabid Curriculum, the teachers in SMK 1 Panjalu Ciamis. The instrument used refers to 21 standard indicator processes in the form of analysis instruments, and interview guidelines. The conclusion in this study is; (1) Profile of achievement of standard process indicators shows results that vary with average achievement of 89%. (2) Indicators that have not yet reached the indicator are related to the teacher using methods, models, and approaches according to the characteristics of the students. The recommendations in this study are that more authentic research is needed on methods, models and learning approaches.